The weakness of backdoor listing regulation and its implications to investors’ protection (comparative study between Indonesia and Hong Kong) - Aisyah, Muethia; Rahadiyan, Inda; Mardhatillah, Siti Ruhama (Universitas Ahmad Dahlan, 2024)
Introduction to the Problem: Backdoor listing is an alternative way for private companies to be listed on the stock exchange by taking over public companies and changing the company's business line without an IPO process. Backdoor listing has not been specifically regulated in Indonesia, so it has not optimally protected investors' investment security. However, the practice of backdoor listing is commonly used. In contrast, The Stock Exchange of Hong Kong Limited (SEHK) has recently issued amended regulations related to backdoor listing that aim to accommodate backdoor listing activities.Purpose/Study Objectives: This research aims to determine the regulation of backdoor listing on the Indonesian Capital Market Regulations.Design/Methodology/Approach: This research uses the normative method or doctrinal legal analysis. The study discusses comparative cases that occur in Hong Kong.Findings: This research concludes there is still a fundamental area for improvement in the regulation of backdoor listing in Indonesia. Backdoor listing is not specifically regulated in Indonesia, but those activities were regulated referred in OJK Regulation Number 32/POJK.04/2015 on Capital Increase of Public Companies with Pre-emptive Rights, OJK Regulation Number 74/POJK. 04/2016 on Business Merger or Consolidation of Public Companies, OJK Regulation Number 9/POJK. 04/2018 on Takeovers of Public Companies. However, in practice, those actions are commonly used. Under certain conditions and cases, this weakness may result in weak guarantees of legal protection for investors. In contrast, backdoor listing in Hong Kong has been adequately regulated, including the requirement for listed issuers to disclose information about the reverse takeover must at an early stage and the requirement for shareholders’ approval.Paper Type: Research Article